A classification of Lejeuneaceae (Marchantiophyta) based on molecular and morphological evidence - Gradstein, S. Robbert (Phytotaxa, 2013)
Lejeuneaceae are the largest family of the liverworts with at least one thousand species in 68 currently accepted genera. The number of genera is much lower than accepted previously and was reduced based on recent molecular work. This paper present a first classification of Lejeuneaceae based on integrated molecular-phylogenetic and morphological evidence. The family is subdivided into two broad subfamilies, Ptychanthoideae (19 genera) and Lejeuneoideae (49 genera). Ptychanthoideae are not further subdivided whereas Lejeuneoideae are classified into three tribes: Brachiolejeuneeae (8 genera), Symbiezidieae (new; 1 genus) and Lejeuneeae (40 genera). Lejeuneeae, the largest tribe in the family, are classified into eight subtribes: Ceratolejeuneinae (2 genera), Cheilolejeuneinae (4 genera), Cololejeuneinae (12 genera), Cyclolejeuneinae (3 genera), Drepanolejeuneinae (2 genera), Echinolejeuneinae (3 genera), Lejeuneinae (5 genera) and Lepidolejeuneinae (2 genera). Seven genera of Lejeuneeae have not yet been studied by molecular methods and are not classified.